A Review Of The Act Of Category-Shifts In Giving An Equivalence In French-Indonesian Novel Translation “Orang Asing” By Albert Camus: English - Ikhwan Zuhdi; Dadang Sunendar (Universitas Cokroaminoto Palopo, 2022)
Translation is an action of transferring message from source language (SL) to target language (TL) by using the translation technique. The equivalence is a key that will help the reader in understanding the author’s information. In other words, the activity of translating must obey the technique and strategy in order to transmitting the real meaning of each sentences. This study aimed to reveal and describe the category-shifts and its purpose in Indonesian translation text of the novel “orang asing” by Albert Camus that has been translated from the French version “étranger”in giving an equivalence to the target language (TL). The focus of this study is to identify the type of category-shifts such as “structure-shifts, unit-shifts, class-shifts and intra-system-shifts” using the theory of Catford (1978). The methods using in this study is a qualitative design by Kothari (2004) which intend to do a literature study and observation in the data source. The result of the analysis shows that there are many shifting appear from the source language (SL) to the target language (TL). The first aspect provoke this shifting is the culture of the translators and the second aspect is influenced by the translator’s language style.